STRATEGIC LANDMARKS OF MOSCOW REGION DEVELOPMENT BASED ON SELF-GOVERNANCE AND COOPERATION - Galina M. Zinchuk; Anara S. Makekadyrova; Alla N. Stolyarova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies lines of strategic development of the territory of the Moscow region, shows target landmarks of its joint development with other entities of the Federation. By calculating employment and level of population servicing the authors identify the resource components of improving the process of cooperation development on the territory. They analyze strong points of the existing model of developing certain territories with high dependence on budget financing. The authors propose mechanism of self-governance and self-organization as a new form of managing territorial development together with other systems to improve a standard of living of the population.